Manajemen Penghimpunan dan Pendistribusian Dana ZIS Di LAZISNU Kota Padangsidimpuan - Sitompul, Risna Hairani; Butar-Butar, Ade Awari; Lbs, Wenni Sakinah (Journal of Islamic Social Finance Management, 2021)
Indonesia is the largest Muslim population so Indonesia has the potential for ZIS funds. Funding sources from ZIS funds can be used to strengthen economic empowerment, distribute income and drive the economy. Research objectives to determine the management of fundraising through the KOIN NU movement, social media, payment accounts, and barcodes, to know the distribution of funds raised by LAZISNU under the LAZISNU Padangsidimpuan implementation program. The research method is carried out qualitatively with primary data: conducting direct interviews from sources and secondary data in the form of evidence of recording, bookkeeping, and data regarding research. The results of the research were using the KOIN NU movement, social media, accounts, and payment barcodes. The collection of funds with KOIN NU which is spread across several areas in North Sumatra Province has increased and resulted in higher funds collected than others. Fund management is carried out carefully and is recorded in detailed books regarding the amount and infak received and the distribution of these funds for each activity. Funds are collected twice a week. LAZISNU Padangsidimpuan fund distribution in 5 fields, namely socio-religion, economy, education, renovation, and health. Keywords: Fund, Fundraising, Distribution, LAZISNU, ZIS